The Movement Structure of Digul Dance in Tonjong Village, Tonjong District, Brebes Regency - Paranti, Lesa; Nahdiah, Dina (Jurnal Pendidikan Sendratasik, 2025)
Tari Digul is an early creative dance that has developed in Tonjong District, Brebes Regency, since the early days of Indonesia’s independence. One of the art groups that continues to preserve this dance is the Forum Pemuda Pemudi Kartika Kesenian Digul Tonjong, located in Tonjong Village. The purpose of this study is to identify and describe the movement structure of Tari Digul in Tonjong Village, Tonjong District, Brebes Regency. This research employs a qualitative descriptive method with a choreographic structural approach. Data collection techniques include observation, interviews, and documentation. Data validity is ensured through source triangulation, technique triangulation, and time triangulation. The data analysis techniques used are the structural analysis methods of Anya Peterson Royce and Sumaryono, further elaborated with Janed Adshead’s dance analysis techniques. The findings of this study reveal that the movement structure of Tari Digul refers to elements of dance movement, namely movement motifs, movement phrases, movement sentences, and the largest unit, movement clusters. It also considers the relationships between basic dance elements, body parts involved, movement types, and movement qualities or character. Tari Digul consists of 12 movement sentences, 12 phrases, and 66 movement motifs that are interconnected, forming a unified whole dance composition. Based on this, Tari Digul clearly exhibits a hierarchical relationship between its movement elements, which includes syntagmatic, paradigmatic, and overlapping relationships